FAKTOR-FAKTOR PENGHAMBAT DALAM PENERAPAN PERENCANAAN PAJAK DI CV MAITRI HARMONIS JAYA - Lumentah, Natalie Reyne (Restitusi : Jurnal Riset Perpajakan, 2022)
This study aims to determine the inhibiting factors in the application of tax planning at CV Maitri Harmonis Jaya. The data in this study were obtained from observations and interviews from CV Maitri Harmonis Jaya. This study uses primary data obtained directly by conducting interviews and observations on the company as the object of research. The data analysis method used is descriptive. The results showed that: The inhibiting factors in the implementation of tax planning at CV Maitri Harmonis Jaya were Tax Socialization and Understanding of Tax Procedures.